PSIKOLOGI SPIRITUAL ZAKAT DAN SEDEKAH - Nurjannah Nurjannah (istinbath, 2018)
In the verse of the zakat commands (Q.S. At-Taubah: 130) there is animportant word of ‘cleansing’, ‘sanctifying’, ‘praying’ and ‘serenity’, after theword zakat. It can be assumed that the practice of zakat is closely related tothe psychological matters of those four things. Therefore, this study deals withkinds of spiritual-psychological dynamics underlying a person to be willing orreluctant to pay zakat and alms. Based on the findings, this study furthermoreconcerns on whatMuslim clerics should do to the Muslim community in orderto be aware of zakat and alms.This study thus examines Islamic teachings aboutzakat and alms. The main sources are taken from Islamic literature especiallyfiqh and al-Qur’an equipped with psychology literature to explore the spiritthat gives birth to the behavior. The study is conducted in depth using contentanalysis, with an Islamic spiritual-psychology approach. Itfinds that in theteachings of zakat and alms contains the guiding spirit of the implementationto achieve the function of zakat and alms as a means of social welfare. Themain key lies in the spirit of unity which eventually forms spiritual, moral,social and emotional intelligence in alms giving. The positive spirit is born onthe spiritual-psychological dynamics,winning the voice of the spirit of divinetruth as a form of the believer’s character, from the evil’s whisper as a form ofkufr. In accordance with these findings, clerics are tasked with guiding humanbeings into meaningful benefactors in the eyes of fellow men and God, byproviding spiritual-psychological guidance of managing the voice of truthagainst the lust of satan and managing the emotions and morals. Pada ayat perintah zakat (Q.S. At-Taubah: 130) terdapat kata pentingyakni ‘membersihkan’, ‘menyucikan’ ‘mendoa’ dan ‘ketentraman jiwa’,setelah kata zakat. Ini bisa diasumsikan bahwa pengamalan zakat berkaitanerat dengan hal-hal psikologis spiritual empat hal tersebut. Maka kajian inimempertanyakan: Dinamika psikologis spiritual seperti apa yang mendasariseseorang beresedia atau enggan membayar zakat dan sedekah? Berdasarkanhasil kajian tersebut, apa yang mesti dilakukan agamawan kepada masyarakatmuslim supaya sadar berzakat dan bersedekah? Guna menjawab pertanyaantersebut, tulisan ini mengkaji ajaran Islam tentang zakat dan sedekah. Sumberutama berasal dari literatur keislaman khususnya fikih dan al-Qur’an dilengkapiliteratur psikologi guna menggali spirit yang melahirkan perilaku. Kajiandilakukan secara mendalam menggunakan analisis isi, dengan pendekatanpsikologi spiritual Islam. Kajian ini menemukan bahwa pada ajaran zakat dansedekah termaktup spirit penuntun pelaksanaannya guna mencapai fungsizakat dan sedekah sebagai sarana kesejahteraan sosial. Kunci utama terletakpada spirit ruh tauhid yang melahirkan keceerdasan spiritual, moral, sosialdan emosional dalam berderma. Spirit positif tersebut lahir atas dinamikapsikologis spiritual memenangkan suara ruh kebenaran ilahiyah sebagai bentuksifat mukmin, dari bisikan tipudaya nasfu syetan sebagai bentuk sifat kufur.Sesuai temuan tersebut, agamawan bertugas membimbing manusia menjadipenderma bermakna di mata sesama dan Allah, yakni dengan memberikanbimbingan psikologis spiritual mengelola suara kebenaran melawan suaranafsu syetan serta mengelola emosi dan moral.